2008
DOI: 10.1017/s0022215108003666
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of xylometazoline (Otrivine) and phenylephrine/lignocaine mixture (Cophenylcaine) for the purposes of rigid nasendoscopy: a prospective, double-blind, randomised trial

Abstract: Phenylephrine-lignocaine mixture is considerably more expensive and has potentially more side effects than xylometazoline. These study findings suggest that it is difficult to justify the use of phenylephrine-lignocaine mixture over xylometazoline, for nasal preparation prior to rigid nasendoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In contrast, other studies have investigated the use of a sole vasoconstrictor or decongestant. Xylometazoline is a cheap decongestant with few side‐effects, although not as efficacious as anaesthetic alone, and can be used to improve tolerance and ease of procedure by widening the nasal aperture …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have investigated the use of a sole vasoconstrictor or decongestant. Xylometazoline is a cheap decongestant with few side‐effects, although not as efficacious as anaesthetic alone, and can be used to improve tolerance and ease of procedure by widening the nasal aperture …”
Section: Discussionmentioning
confidence: 99%
“…Topical nasal vasoconstriction with oxymetazoline is considered to have similar or greater efficacy and less toxicity (hypertension, tachycardia) compared with phenylephrine, epinephrine, and cocaine, especially in children . Thus, it is a frequently used topical vasoconstrictor in intubations and surgeries involving the nasal passages and is often considered by clinicians to be a benign drug.…”
Section: Discussionmentioning
confidence: 99%
“…We only compared 4% cocaine to 0.5% phenylephrine. However, recent trials have shown promising results of 2% tetracaine in combination with epinephrine,[18] 0.1% xylometazoline[19] and 0.05% oxymetazoline[20] as nasal decongestants. Thus, future research should be directed at comparing all these agents side by side in a randomised fashion with a well-planned comparative analysis.…”
Section: Discussionmentioning
confidence: 99%